A study of African traditional gamesas informal education: The case of mahumbwe, mabombo and nhodo in Mandeya District of Matsapa: 1945 to 2016. - Kuyimba, James (Midlands State University, 2018)
The study examines the position of traditional games as a form of informal education in Zimbabwe, with a particular focus to Matsapa in the HondeValley region. African traditional games was an important educative tool which was used during the pre-colonial era to teach children real life experiences and instill life skills in them which would carry them the rest of their life The study makes use of qualitative research design using key informant, unstructured in-depth interviews and a review of secondary data sources. The study reveals that the importance of African traditional games is deteriorating day by day as a result of a plethora of factors for instance westernization and globalization. Children of today have adopted western life styles and the things they now learn in educational institutions are no longer at par with their culture. By so doing there is greater need to come up with frameworks which help enhance the knowledge and preserve the existence of traditional games as a form of informal education for generations and future generations to come.